Creating a geodemographic classification model within geo-marketing: the case of Eskişehir province - Ergun, Mustafa; Uyguçgil, Hakan; Atalik, Özlem (Bulletin of Geography. Socio-economic Series, 2020)
Businesses today face great competition in their operations, making it necessary for them to adopt a “customer-oriented” approach. In this competitive environment, where customers are more valuable, enterprises accrue great advantages from an understanding of the characteristics of the target audience in all dimensions. This is where the importance of geo-marketing and demographic segmentation for enterprises emerges. This study performed a geo-demographic segmentation of the urban neighbourhoods of Eskişehir province and sought to determine the characteristics of the people living in these neighbourhoods at the household level. The Groups created using the SPSS package program as well as Principal Components Analysis (PCA) and Hierarchical Clustering Analysis were then mapped on the GIS platform as urban neighbourhoods.